حماية المستهلك من المضاربة في ظل قانون 21/15 - زبدي أمال; معتوقي مباركة (My University, 2023)
تهدف هذه الدراسة إلى تناول أحكام القانون رقم: 21-15 المتعلق بمكافحة المضاربة غير المشروعة في الجانب الخاص بحماية المستهلك من هذه الجريمة، التي أثرت سلبيا على قدرته الشرائية لندرة مواد الاستهلاك الأساسية وما صاحب ذلك من الارتفاع المفرط لأسعارها، فعلى الرغم من انتشارها في السنوات الأخيرة، لم تجد من النصوص التشريعية التي تتصدى لها باستثناء ما جاء في قانون العقوبات من قواعد عامة التي عرفت قصورا في ضمان حماية الحقوق الاقتصادية للمستهلك، لذلك سن المشرع الجزائري هذا القانون محددا لصور المضاربة غير المشروعة وأركانها، واعتباره نص جنائي خاص جاء متضمنا في شقه الموضوعي أحكاما تجريمية وعقابية وإدارية تميزت بالتشدد، كما جعل مهمة مكافحة هذه الجريمة مشتركة بهدف حماية المستهلك وضمان إعادة التوازن للسوق.Thisstudyaims to address the provisions of Law No: 15-21 related to combating illegal speculation in the aspect of protecting the consumer from this crime, which negatively affected his purchasing power due to the scarcity of basic consumer goods and the accompanying excessive rise in their prices, despite its spread in recent years, You did not find any legislative texts that deal with it, except for what was stated in the Penal Code of general rules that were known for failure to ensure the protection of the economic rights of the consumer, so the Algerian legislator enacted this law specifying the forms of illegal speculation and its pillars, and considering it a special criminal text that came included in the substantive part of the provisions Criminal, punitive and administrative characterized by strictness. He also made the task of combating this crime joint with the aim of protecting the consumer and ensuring the restoration of balance to the market.
مذكرة ماستر
Keywords: مضاربةغيرمشروعة، السوق، المستهلك،الاحتكار،المشرعقانون 21_15; illegalspeculation, market, consumer, monopoly, legislator Law 21_15.